Effect of early mobilization on post SC pain (a literature review) - Idawati Idawati; Dian Khaironnisa; Siti Aisyah; Nurul Husna; Devi Setiawati (Institute of Computer Science (IOCS), 2023)
Early mobilization is a way to make patients independent so that patients are able to carry out their own activities without the help of others. Pain management can be pharmacological, non-pharmacological. Nonpharmacological techniques used to reduce postoperative pain are early mobilization techniques. This study was to determine the effect of early mobilization on Post SC pain. The method used is a literature review using the Google Scholar and PubMed databases by identifying 20 articles on the same topic in the 2018-2022 range and filtering them so that their feasibility is assessed and 15 articles are appropriate. Literature search used the keywords SC surgery, early mobilization. The results obtained from this literature study have the effect of mobilization on Post SC Pain patients, namely the application of one of the non-pharmacological techniques that can be used to reduce postoperative pain is the early mobilization technique. Based on the process, there was a significant difference in the effect of the results of early mobilization on the pain scale in post SC mothers. Early mobilization in post sectio caesarea patients can improve blood circulation so that the wound tissue becomes better. The faster the post-SC mother moves, the faster wound will heal. The limitations encountered during compiling this literature review were the difficulties in finding literature or sources that matched the guidelines and adjusting the title of the literature review with the inclusion criteria. It is hoped that future work researchers can learn more about early mobility in post-sc patients from different journals.